Equestrian expertise affecting physical fitness, body compositions, lactate, heart rate and calorie consumption of elite horse riding players - Sung, B.-J.; Jeon, S.-Y.; Lim, S.-R.; Lee, K.-E.; Jee, H. (Journal of Exercise Rehabilitation, 2015)
Horse riding (HR) is a sport harmonized with rider and horse. HR is renowned as an effective sport for young and old women and men. There is rare study regarding comparison between elite horse riders and amateurs. We aimed to investigate comprehensive ranges of parameters such as change of lactate, heart rate, calorie, VO2max, skeletal muscle mass, body water, body fat, etc between amateurs and professionals to emphasize HR not only as a sport training but also as a therapeutic aspect. We performed 3 experiments for comparing physical fitness, body compositions, lactate value, heart rate and calorie consumption change before and after riding between amateurs and elites. Around 3 yr riding experienced elites are preeminent at balance capability compared to 1 yr riding experienced amateurs. During 18 min horse riding, skeletal muscle mass and body fat were interestingly increased and decreased, respectively. Lactate response was more sensitive in elites rather than amateurs and its recovery was reversely reacted. Exercise intensity estimated from heart rate was significantly higher in elites (P<0.05). The similar pattern of calorie consumption during riding between amateurs and elites was shown. Horse riding possibly induces various physiological (muscle strength, balance, oxidative capability, flexibility, and metabolic control) changes within body and is thus highly recommended as combined exercise for women, children, and aged as therapeutic and leisure sport activity.